Field-realistic acute exposure to glyphosate-based herbicide impairs fine-color discrimination in bumblebees - Helander, Marjo; Lehtonen, Topi K.; Saikkonen, Kari; Despains, Léo; Nyckees, Danae; Antinoja, Anna; Solvi, Cwyn; Loukola, Olli J. (Elsevier BV, 2023)
Pollinator decline is a grave challenge worldwide. One of the main culprits for this decline is the widespread use of, and pollinators' chronic exposure to, agrochemicals. Here, we examined the effect of a field-realistic dose of the world's most commonly used pesticide, glyphosate-based herbicide (GBH), on bumblebee cognition. We experimentally tested bumblebee (Bombus terrestris) color and scent discrimination using acute GBH exposure, approximating a field-realistic dose from a day's foraging in a patch recently sprayed with GBH. In a 10-color discrimination experiment with five learning bouts, GBH treated bumblebees' learning rate fell to zero by third learning bout, whereas the control bees increased their performance in the last two bouts. In the memory test, the GBH treated bumblebees performed to near chance level, indicating that they had lost everything they had learned during the learning bouts, while the control bees were performing close to the level in their last learning bout. However, GBH did not affect bees' learning in a 2-color or 10-odor discrimination experiment, which suggests that the impact is limited to fine color learning and does not necessarily generalize to less specific tasks or other modalities. These results indicate that the widely used pesticide damages bumblebees' fine-color discrimination, which is essential to the pollinator's individual success and to colony fitness in complex foraging environments. Hence, our study suggests that acute sublethal exposure to GBH poses a greater threat to pollination-based ecosystem services than previously thought, and that tests for learning and memory should be integrated into pesticide risk assessment.
Keywords: Glyphosate; Bumblebee; Pollinator decline; Color discrimination; Odor discrimination